No plate tectonic shutdown in the early Paleoproterozoic: Constraints from the ca. 2.4 Ga granitoids in the Quanji Massif, NW China. (1st April 2019) - Gong, Songlin; He, Chuan; Wang, Xuan-Ce; Chen, Nengsong; Kusky, Timothy
Graphical abstract: Highlights: 2.4 Ga granitoids of the Quanji Massif show high-K I-type and A2 -type affinities. The magmas were derived from early Paleoproterozoic juvenile crust and ancient crust. The plate tectonics did not shut down during the early Paleoproterozoic. Abstract: The global plate tectonic regime in the early Paleoproterozoic period is highly debated. Granitoids bear key information to address such a debate. Petrological, geochemical and geochronological studies are conducted on two post-collisional granitoid plutons in the Quanji Massif, northwestern China, to investigate the tectonic regime during this period. The granitoids are composed of syenogranite, monzogranite, and granodiorite, with minor tonalite, which intruded into the Delingha and Hudesheng regions at ca. 2.39–2.37 Ga. These plutons are high-K I-type granitoids with variable Ga/Al ratios, showing some characteristics of A2 -type granitoids. They are characterized by enrichment of LILEs and LREEs and depletion of Sr, P, Ti, and Eu. They show depleted Nd and Hf isotope signatures with whole rock εNd (t) = +0.7 to +4.8 and zircon εHf (t) = −1.0 to +7.8, indicating a juvenile crustal growth event at ca. 2.44–2.37 Ga. Our new results together with other coeval post-collisional granitoids in the Quanji Massif suggest that the protracted post-collisional magmatism at ca. 2.39–2.34 Ga occurred just after a short interval of subduction and generation of juvenile magmas before or around ca. 2.4 Ga. Collectively, the formation of these ca. 2.4–2.3 Ga granitoids in the Quanji Massif may correlate with coeval granitoids in the Tarim and North China cratons, and is broadly coeval with magmatism in several other cratons in the West African and Canadian Shields. Thus, the globally well-documented magmatism at early Paleoproterozoic, or Siderian, provides further information for filling up the age gap of the so-called plate tectonic "shutdown" in the early Paleoproterozoic period worldwide. The geologic record therefore suggests no Siderian shutdown of plate tectonics, but instead, continuous global subduction and generation of juvenile magmas from the Archean through the Paleoproterozoic.